Tren Pengembangan Sistem Pendukung Keputusan Metode Simple Additive Weighting: Systematic Literature Review - Rahman, Ikhlasul Aulia (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
The advancements in digital transformation era have impacted the complexity of decision-making processes across various sectors, especially with the increasing volume of large and diverse data. In this context, efficient tools were required to objectively evaluate multi-criteria alternatives. Simple Additive Weighting (SAW) emerged as one of the most widely used methods in Decision Support Systems (DSS). However, systematic reviews discussing the development and implementation of this method in various contexts remained very limited. This study aimed to conduct a Systematic Literature Review (SLR) on the development of SAW-based DSS with a focus on identifying application platforms, design methods, and their benefits. This study employed a Systematic Literature Review approach following the Kitchenham guidelines. The findings showed that web-based platforms dominated DSS development due to their flexibility, accessibility, and ability to support real-time decision-making. Furthermore, the Prototyping design method was frequently used as it allowed dynamic adjustments of the system to meet user needs. The application of the SAW method consistently demonstrated improvements in accuracy, time efficiency, transparency, and user trust in the decision-making process.